2022
DOI: 10.1371/journal.ppat.1010926
|View full text |Cite
|
Sign up to set email alerts
|

Piperaquine-resistant PfCRT mutations differentially impact drug transport, hemoglobin catabolism and parasite physiology in Plasmodium falciparum asexual blood stages

Abstract: The emergence of Plasmodium falciparum parasite resistance to dihydroartemisinin + piperaquine (PPQ) in Southeast Asia threatens plans to increase the global use of this first-line antimalarial combination. High-level PPQ resistance appears to be mediated primarily by novel mutations in the P. falciparum chloroquine resistance transporter (PfCRT), which enhance parasite survival at high PPQ concentrations in vitro and increase the risk of dihydroartemisinin + PPQ treatment failure in patients. Using isogenic D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 88 publications
4
30
0
Order By: Relevance
“…Whilst the targets of MMV1557817 were confirmed using the above methods, it is also important to assess the ability of parasites to become resistant to the compound and the potential impact this has on other antimalarial drugs. Recent in vitro resistance selection and whole genome analysis undertaken to determine if resistance against MMV1557817 could be selected in Dd2 parasites identified a A460S mutation in one of its intended targets, Pf A-M17, as well as a N846I mutation in an AP-3 β subunit (PF3D7_0613500) and a M317I mutation in a non-essential conserved Plasmodium protein (PF3D7_1144400) (61). These three mutations were present in all clones obtained from multiple flasks, with parasites only displaying modest IC 50 shifts of between 1.5 – 2.9x, suggesting a low level of resistance (61).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst the targets of MMV1557817 were confirmed using the above methods, it is also important to assess the ability of parasites to become resistant to the compound and the potential impact this has on other antimalarial drugs. Recent in vitro resistance selection and whole genome analysis undertaken to determine if resistance against MMV1557817 could be selected in Dd2 parasites identified a A460S mutation in one of its intended targets, Pf A-M17, as well as a N846I mutation in an AP-3 β subunit (PF3D7_0613500) and a M317I mutation in a non-essential conserved Plasmodium protein (PF3D7_1144400) (61). These three mutations were present in all clones obtained from multiple flasks, with parasites only displaying modest IC 50 shifts of between 1.5 – 2.9x, suggesting a low level of resistance (61).…”
Section: Resultsmentioning
confidence: 99%
“…Recent in vitro resistance selection and whole genome analysis undertaken to determine if resistance against MMV1557817 could be selected in Dd2 parasites identified a A460S mutation in one of its intended targets, Pf A-M17, as well as a N846I mutation in an AP-3 β subunit (PF3D7_0613500) and a M317I mutation in a non-essential conserved Plasmodium protein (PF3D7_1144400) (61). These three mutations were present in all clones obtained from multiple flasks, with parasites only displaying modest IC 50 shifts of between 1.5 – 2.9x, suggesting a low level of resistance (61). To confirm whether the A460S mutation was responsible for resistance, CRISPR/Cas9 technology was utilised to attempt to introduce this mutation into Pf A-M17 in Pf 3D7 wildtype parasites using a previously described donor plasmid method (62).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our comprehensive results indicate that halofuginone damages biological pathways and induces autophagy in E. tenella. Previous studies also found that differential expression of regulated genes may lead to differences in drug-resistant and drug-sensitive strains (Antony et al, 2016;Ingham et al, 2020;Xie et al, 2020;Laing et al, 2022;Okombo et al, 2022;Zhang et al, 2022). Hence, it was expected that long-term selection would lead to transcriptional changes in different genes in the resistant strain.…”
Section: Discussionmentioning
confidence: 98%
“…Resistance to CQ historically is mainly facilitated by genetic changes within the coding region of the gene encoding a transporter on the parasite food vacuole membrane; the Plasmodium falciparum chloroquine resistance transporter (PfCRT) gene. This transporter is responsible for the influx/efflux of some antimalarial drugs to and from the food vacuole of the parasite [30][31][32]. Point mutations that translate to changes in amino acids at different positions have contributed to the parasites' competence to resist drugs such as chloroquine and structurally related antimalarial drugs [ [30,33,34].…”
Section: Introductionmentioning
confidence: 99%